2014
DOI: 10.1371/journal.pone.0084387
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Simvastatin Rescues Retinal Ganglion Cells from Optic Nerve Injury Possibly through Suppression of Astroglial NF-κB Activation

Abstract: Neuroinflammation is involved in the death of retinal ganglion cells (RGCs) after optic nerve injury. The purpose of this study was to determine whether systemic simvastatin can suppress neuroinflammation in the optic nerve and rescue RGCs after the optic nerve is crushed. Simvastatin or its vehicle was given through an osmotic minipump beginning one week prior to the crushing. Immunohistochemistry and real-time PCR were used to determine the degree of neuroinflammation on day 3 after the crushing. The density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
(52 reference statements)
1
30
0
Order By: Relevance
“…An indirect effect through effects on cardiovascular disease cannot be ruled out given that cardiovascular disease in itself has been shown to increase disability progression in progressive MS [64], possibly due to vascular disease-induced peripheral inflammation, which by itself has been linked to brain atrophy [65]. A possible explanation for a more marked effect of statins in neurodegeneration and atrophy in progressive MS than in RRMS may be a more marked effect on monocytes, rather than lymphocytes, as the presence of activated microglia is a pathological hallmark of progressive MS. A possible mechanism of effect of statins on monocyte-induced injury in the CNS has been outlined above [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect effect through effects on cardiovascular disease cannot be ruled out given that cardiovascular disease in itself has been shown to increase disability progression in progressive MS [64], possibly due to vascular disease-induced peripheral inflammation, which by itself has been linked to brain atrophy [65]. A possible explanation for a more marked effect of statins in neurodegeneration and atrophy in progressive MS than in RRMS may be a more marked effect on monocytes, rather than lymphocytes, as the presence of activated microglia is a pathological hallmark of progressive MS. A possible mechanism of effect of statins on monocyte-induced injury in the CNS has been outlined above [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, a later murine study indicated a marked effect of statins on RGC survival after damage to the optic nerve. In this study, systemic simvastatin was shown to lead to local changes at the region of the optic nerve in the form of decreased levels of monocyte chemoattractant protein (MCP)-1 (an astrocytal chemokine involved in recruiting monocytes), suppressed numbers of monocytes, decreased upregulation of proinflammatory TNFa, and decreased TNFa-activated nuclear factor (NF)-jB astroglial activation [29].…”
Section: Neuroprotective Actions Of Statinsmentioning
confidence: 99%
“…Astrocytes were isolated from the optic nerves of Wistar rats according to published procedures, with some modifications [25]. In brief, the left optic nerves of 6 rats were crushed under anesthesia with intraperitoneal pentobarbital sodium to make the astrocytes reactive.…”
Section: Methodsmentioning
confidence: 99%
“…The purity of the astrocytes of cells at passage 3 was determined by immunoreactivity to glial fibrillary acidic protein (GFAP) and flow cytometry (FACS). The results showed that >96% of the cells were GFAP positive, indicating that our cultures were nearly pure cultures of astrocytes [25]. The astrocytes at passages 3-6 were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…19,24 To quantify the degree of inflammation after the injury in each experimental group, we determined the changes in the expression of CD68 and MCP-1 in the optic nerve by real-time PCR (RT-PCR) on day 7 after the ONC. In addition, the mRNA level of TNF-a was determined because activated microglia and macrophages release inflammatory cytokines.…”
Section: Changes In Expression Of Cd68 Mcp-1 and Tnf-a Genes In Optmentioning
confidence: 99%